Effects of Probiotic Supplementation on Inflammation and Oxidative Stress for Gestational Diabetes: A Meta-Analysis Study - Wang, Jing; Zhang, Yin; Wang, Yan (Zeitschrift für Geburtshilfe und Neonatologie, 2022)
Background Probiotic supplements may benefit to reduce inflammation and oxidative stress in patients with gestational diabetes, and this meta-analysis aims to explore the impact of probiotic supplementation on inflammation and oxidative stress for gestational diabetes.Methods PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases were systematically searched, and we included randomized controlled trials (RCTs) assessing the effect of a probiotic supplement on inflammation and oxidative stress in patients with gestational diabetes.Results Five RCTs were finally included in the meta-analysis. Overall, compared with control intervention for gestational diabetes, probiotic supplementation intervention showed significantly reduced CRP (MD=−1.72; 95% CI=−2.54 to −0.90; P<0.0001), IL-6 (MD=−0.42; 95% CI=−0.66 to −0.18; P=0.0005) and MDA (MD=−0.88; 95% CI=−1.10 to −0.66; P<0.00001), increased NO (MD=2.42; 95% CI=0.80 to 4.04; P=0.003) and TAC (SMD=0.86; 95% CI=0.19 to 1.54; P=0.01), but showed no obvious impact on GSH (MD=13.73; 95% CI=−35.84 to 63.31; P=0.59).Conclusions Probiotic supplementation is effective to alleviate inflammation and oxidative stress for gestational diabetes.
Keywords: probiotic supplement; gestational diabetes; inflammation; oxidative stress